PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI PENGUNGSI DI KEPULAUAN RIAU TAHUN 2015-2017 - Marlina, Leny; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Every country that occurs in a conflict allows for a number of casualties to arise, and victims, especially their countries have fled to other countries. International Organizational for Migration (IOM) is an international organization between governments in this case required play a role in protecting refugees. The data of research obtained from some resources such as, books, journals, official documents, and website to support the hypothesis. The researcher will be used pluralist perspective and analisysis of organizational group. The theory used in this research is the theory of international organization. the method this research will be used qualitative research method. Based on the analysis that found from literature studies and field studies by direct interview with considered information about this study. The result of this research to show that International Organization for Migration (IOM) has important role in handling refugee in Kepulauan Riau, such as facilitating refugee shelters, food assistance, voluntarily return of refugee, providing healt services and so on. Keywords: Role, Refugee, IOM, Kepulauan Riau, International Organization.